How cooperative was the spirit? A note on the Eichengreen-view of Europe after World War II - Karl-Heinz Paqué (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1995)
This paper is an empirical critique of Barry Eichengreen's interpretation of the exceptional growth performance of Western Europe during the 1950s and 1960s. The main part of the paper shows that, at least for the important case of West Germany, Eichengreen fs view of a broad-based economic and social consensus as the major reason for moderate wage growth and fast capital accumulation is hardly compatible with the facts. In particular, there is no historical evidence an explicit or implicit tripartite deal between unions, employers and the government to avoid problems of time-inconsistency in commitments to wage moderation.
Keywords: N1; N14; 330; Wirtschaftswachstum; Institutionalismus; Tarifpolitik; Lohnpolitik; Deutschland; Europa